Lives of extraordinary women : rulers, rebels (and what the neighbors thought) - Krull, Kathleen; Hewitt, Kathryn (San Diego : Harcourt, 2000)
Not all governments have been run by men. Lives of Extraordinary Women turns the spotlight on women who have wielded power, revealing their feats--and flaws--for all the world to see. Here you'll find twenty of the most influential women in history: queens, warriors, prime ministers, first ladies, revolutionary leaders. Some are revered. Others are notorious. What were they really like? In this grand addition to their highly praised series, Kathleen Krull and Kathryn Hewitt celebrate some of the world's most noteworthy women, ranging from the famous to those whose stories have rarely been told.
b
Keywords: Women -- Political activity -- Biography -- Juvenile literature; Women heads of state -- Biography -- Juvenile literature